Macronutrient deficiencies in Italian Pumpkin (Cucurbita pepo L.): symptoms and growth characterization (Research, Society and Development, 2020)
Plants need essential elements for their life, due to the various functions that these elements perform. To describe and evaluate the symptoms of macronutrient deficiency in Italian squash through visual diagnosis and to evaluate growth parameters. The statistical design used was the DIC with three replications, containing 7 treatments, in nutrient solution. The treatments were: complete nutrient solution (control), nutrient solutions with individual omissions of N, P, K, Ca, Mg and S. After germination, the seedlings were transferred to the complete nutrient solution with 10% of their ionic strength. (adaptation period), which remained under constant aeration. Subsequently, they were transplanted to plastic vessels (8L) with nutrient solution. The observed symptoms were photographed and described. After the manifestation of visual deficiency symptoms, the treatment plants were harvested. The omission of nutrients N, P, K, Ca and Mg in nutrient solution results in morphological changes, translated into characteristic symptoms of deficiency of each nutrient. Macronutrient omission affects the parameters of growth and dry matter production of Italian squash. In general, the omission of macronutrients that most affect the different parts of plants was N and P.